Analisis Hukum Kepemilikan Saham Non-Muslim Pada Perusahaan Syariah Menurut Pandangan Imam Syafi’i - Suardi, Faisal; Fikrih, Muh. Haikal; Waode, Riski Berlian (Fawaid : Sharia Economic Law Review, 2025)
This study examines Imam al-Shafi'i’s perspective on non-Muslim share ownership in Muslim-owned companies through a library research method. The primary focus is to explore classical fiqh views on modern economic phenomena, particularly regarding the concept of syirkah (partnership) and interfaith share ownership. Data collection was conducted through a critical review of primary sources, including Imam al-Shafi'i’s classical fiqh texts, and secondary sources consisting of contemporary literature discussing Islamic economic thought. The research applies a qualitative approach using descriptive-comparative analysis to interpret Imam al-Shafi'i’s views in the context of modern muamalah (economic transactions). Data analysis was carried out using content analysis by identifying, categorizing, and interpreting fundamental concepts in Imam al-Shafi'i’s thought related to partnership and share ownership. The findings show that Imam al-Shafi'i offers a comprehensive approach to non-Muslim share ownership, considering core Sharia principles, business integrity, and economic impact. He emphasizes the importance of evaluating business objectives, ownership proportions, and fairness in interfaith business transactions. This research contributes to the development of contemporary fiqh understanding in Islamic economics, especially within the increasingly complex context of economic globalization. Keywords: Imam al-Shafi'i, Share Ownership, Non-Muslim, Syirkah